2017
DOI: 10.5530/ijper.51.3s.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Histology and Nutrient Digestibility of Supplemented Origanum onites Essential Oil to Rainbow Trout Diets (Oncorhynchus mykiss)

Abstract: The present experiment was conducted to describe the effects on histology (experiment 1) and nutrient digestibility (experiment 2) of rainbow trout fed with diet containing O. onites oil. Diets were prepared with supplemented in different concentrate (0, 0.125, 1.5, 2.5, 3.0 ml kg -1 ) of O. onites oil. A total of 1050 trout (body weight 26.05 ± 0.15 g) were randomly stocked into 15 tanks. The experiments were done in triplicate.In the experiment 1, rainbow trout were fed during 90 day for histology analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
7
0
4
Order By: Relevance
“…In our study, vacuolization was observed in hepatocyte cells with the addition of laurel oil. Similar to our study, it was observed in tambaqui fry-fed 1.0 mL kg -1 ginger EO (Chung et al, 2021) and rainbow trout fed with Origanum onites essential oil (Yigit et al, 2017). However, in the tilapias examined, no pathological picture such as necrosis was found in hepatocyte cells reported by these researchers.…”
Section: Histological Examinationsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, vacuolization was observed in hepatocyte cells with the addition of laurel oil. Similar to our study, it was observed in tambaqui fry-fed 1.0 mL kg -1 ginger EO (Chung et al, 2021) and rainbow trout fed with Origanum onites essential oil (Yigit et al, 2017). However, in the tilapias examined, no pathological picture such as necrosis was found in hepatocyte cells reported by these researchers.…”
Section: Histological Examinationsupporting
confidence: 90%
“…Intestinal anatomy and histology are very important for nutritional evaluation and immunological functions in fish health. Therefore, histological examination of the gut can be considered a potential indicator of the overall health of the fish and the efficacy of feed additives (Yigit et al, 2017;Abdel-Latif et al, 2021;Acar et al, 2021).…”
Section: Intestinal Tissuementioning
confidence: 99%
“…Histopathological experiments play an important role in exposing improvements in fish tissues and cells during adverse circumstances [ 26 , 27 ]. Antioxidant, anti-inflammatory, and essential oils derived from plants are used as feed additives because of the characteristics in the fish diets [ 28 , 29 , 30 ]. The liver is largely responsible for lipid metabolism in fish, which involves both fatty acid production and oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz [ 31 ] discovered that high-fat diets trigger liver lipoid degeneration (steatosis) in carp ( Cyprinus carpio ). In addition, hepatocyte cytoplasmic vacuolation has been observed in the livers of rainbow trout fed with Origanum onites essential oil-supplemented (2.5 mL kg −1 ) diets for 90 days [ 28 ]. The liver histopathological examination in the current study did not reveal any significantly differences in lesions other than lipid vacuole accumulation between the experimental groups ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, Yigit et al (2017) reported necrosis or degeneration in liver of rainbow trout O. mykiss fed a diet containing Origanum onites essential oil at the highest concentrations (1.5, 2.5 and 3 mL kg -1 ). At the time, the researchers highlighted that in high concentrations O.…”
Section: Notementioning
confidence: 95%